2014
DOI: 10.1186/1472-6874-14-108
|View full text |Cite
|
Sign up to set email alerts
|

How risky are second trimester clandestine abortions in Cameroon: a retrospective descriptive study

Abstract: BackgroundComplications of clandestine abortions increase with gestational age. The aim of this study was to identify complications of second trimester clandestine abortions (STA) and those of first trimester clandestine abortions (FTA).MethodsThis retrospective descriptive study was conducted between March 1st and August 31st, 2012 in the University Teaching Hospital and the Central Hospital, Yaoundé (Cameroon). The files of women with clandestine abortions carried out outside our units, but received in our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Only one study reported case fatality by abortion method, with only two deaths reported among women where the method of abortion was ‘not known’. 16 Six studies provided estimates of case fatality by gestational age, 19 20 22–25 and in all studies the case fatality was higher at later gestation (online Supplementary table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported case fatality by abortion method, with only two deaths reported among women where the method of abortion was ‘not known’. 16 Six studies provided estimates of case fatality by gestational age, 19 20 22–25 and in all studies the case fatality was higher at later gestation (online Supplementary table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unsupervised and unsafe abortions continue to be a major cause of maternal morbidity worldwide [2]. In our country, the liberal MTP Act has unfortunately been misused for second-trimester termination of pregnancy following sex determination and has been intricately (and wrongly) related to the PC-PNDT Act.…”
Section: Discussionmentioning
confidence: 99%
“…Under the present restrictive law, it is reasonable to suspect that most of these could be done under unsafe conditions. Reported methods used to induce these unsafe abortions range from transcervical foreign bodies, injections, unspecified medications and diverse plants [ 10 , 11 ]. Women who survive could suffer from infections, uterine and bowel perforations, infertility, sepsis, conditions generally costly to patients and the health system.…”
Section: Introductionmentioning
confidence: 99%